The Influence of Emotional Intelligence and Inhibitory Control on Mathematical Problem-Solving Ability Mediated by Mathematics Anxiety: A Case Study in a 10th-Grade Class at SMA Kemala Bhayangkari - Rino Sinus Pandanu; Asep Nursangaji; Rustam Rustam; Ade Mirza; Dona Fitriawan (Jurnal Pendidikan Indonesia, 2024)
This study is a study aimed at investigating the influence of emotional intelligence and inhibitory control on mathematical problem-solving ability, with math anxiety as an intervening variable. It is a quantitative, ex post facto research that uses questionnaires and tests as research instruments. The study involved 28 students as subjects. The analytical technique used in this study was path analysis. The study results are as follows: (1) There was no significant influence of emotional intelligence on mathematical problem-solving skills, with a p-value = 0,308. (2) There was no significant influence of inhibitory control on mathematical problem-solving skills, with a p-value = 0,956. (3) There was no significant influence of math anxiety on mathematical problem-solving skills, with a p-value = 0,743. (4) There was no significant influence of emotional intelligence on math anxiety, with a p-value = 0,184. (5) There is no significant influence of inhibitory control on math anxiety, with a p-value = 0,701. (6) There was no significant influence of emotional intelligence on mathematical problem-solving skills through math anxiety, with a p-value = 0,804. (7) There was no significant influence of inhibitory control on mathematical problem-solving skills through math anxiety, with a p-value = 0,914.